Guidance for Processing Smoked Seafood in Retail Operations - Keith R. Schneider; Victor Garrido; W. Steve Otwell; Ray Mobley (EDIS)
This recommended guidance is for processing smoked seafood (hot or cold smoked) either as a whole item or in portions, and packaged for display in refrigerated cases for public sale. This document is FSHN05-03, one of a series of the Food Science and Human Nutrition Department, Florida Cooperative Extension Service, IFAS, University of Florida, Gainesville, FL 32611. Published: February 2005.